The effect of operative groups on diabetic foot self-care education: a randomized clinical trial - Moreira, João Batista; Muro, Eliene Sousa; Monteiro, Lidiane Aparecida; Iunes, Denise Hollanda; Assis, Bianca Bacelar de; Chaves, Erika de Cássia Lopes (Revista da Escola de Enfermagem da USP, 2020)
Objective To evaluate the effect of operative groups on teaching self-care for diabetic foot prevention. Method Controlled, blinded clinical trial with volunteers presenting type 2 Diabetes Mellitus, randomized into treatment (55 subjects) and control (54 subjects) groups. The treatment group received the educational intervention “Teaching foot self-care”, whereas the control group was simply evaluated. Feet evaluation was conducted before and after the intervention, as well as 15 days later in a follow-up. The intervention was conducted through an operative group and developed with orientation via writing, explained through dialogue and role-playing. The following tests were used: Shapiro-Wilk, Chi-squared, t-test, Mann-Whitney, McNemar, and paired Wilcoxon. Results One-hundred and nine volunteers took part in this study. Their sociodemographic variables were homogeneous. In an analysis between groups, an improvement was observed after the educational intervention regarding most variables related to skin annexes, blood flow, foot sensitivity, and foot pressure. Improved scores for risk of diabetic foot in the treatment group were observed. Conclusion The educational intervention through operative group was efficient, for it encouraged self-care and reduced potential risk of diabetic foot. Brazilian Registry of Clinical Trials (Registro Brasileiro de Ensaios Clínicos): RBR- 753 Kcg.